Social aspirations in European banks: peer-influenced risk behavior - Štefan Lyócsa; Tomáš Výrost; Eduard Baumöhl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
We test a sample of 3,586 banks from 33 European countries to determine whether performances above or below a social aspiration level (median performance of peer banks) influence banks' aggregate risk levels. Our results are consistent with the behavioral theory of the firm and prospect theory in that we find that bank performance below a bank's social aspiration level is followed by increased aggregate risk, i.e., risk-taking behavior in the subsequent year. Although under-performing banks tend to be risk-takers, large banks and banks with high aggregate risk levels tend to limit the increase in their aggregate risk levels.
Keywords: D22; G2; G41; L22; L25; 330; social aspiration; European banks; performance; risk behavior; prospect theory